2021
DOI: 10.1016/j.cognition.2021.104649
|View full text |Cite
|
Sign up to set email alerts
|

Your health vs. my liberty: Philosophical beliefs dominated reflection and identifiable victim effects when predicting public health recommendation compliance during the COVID-19 pandemic

Abstract: In response to crises, people sometimes prioritize fewer specific identifiable victims over many unspecified statistical victims. How other factors can explain this bias remains unclear. So two experiments investigated how complying with public health recommendations during the COVID19 pandemic depended on victim portrayal, reflection, and philosophical beliefs (Total N = 998). Only one experiment found that messaging about individual victims increased compliance compared to messaging about statistical victims… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 119 publications
(130 reference statements)
3
24
0
Order By: Relevance
“…Previous literature has demonstrated that citizen compliance with preventative measures is influenced by attitudes toward their government and government policies ( Gesser-Edelsburg et al, 2020 ; Salimi et al, 2020 ). Moreover, research regarding health crises response has shown that the success of healthcare policies relies, in part, on the public's perception of personal and societal risk ( Bavel et al, 2020 ; Byrd and Białek, 2021 ; Dryhurst et al, 2020 ). During the current COVID-19 pandemic, risk perception is suggested to be influenced by personal experience, values, and societal and cultural norms ( Al-Hasan et al, 2020 ; Dryhurst et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has demonstrated that citizen compliance with preventative measures is influenced by attitudes toward their government and government policies ( Gesser-Edelsburg et al, 2020 ; Salimi et al, 2020 ). Moreover, research regarding health crises response has shown that the success of healthcare policies relies, in part, on the public's perception of personal and societal risk ( Bavel et al, 2020 ; Byrd and Białek, 2021 ; Dryhurst et al, 2020 ). During the current COVID-19 pandemic, risk perception is suggested to be influenced by personal experience, values, and societal and cultural norms ( Al-Hasan et al, 2020 ; Dryhurst et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, social distancing restrictions elicit a potential clash between the individualizing and binding foundations. If everyone is ordered to comply, someone on the left who values the individualizing foundations over the binding ones will likely do so, in fairness to others and to minimize the harms of viral transmission [44]. Although those on the political right do still value care, they differ regarding to what degree it needs to be balanced with other moral foundations [40].…”
Section: Introductionmentioning
confidence: 99%
“…Since this time, better reflection test performance has predicted moral judgments about unintended side effects (Pinillos, Smith, Nair, Marchetto, & Mun, 2011), a tendency toward atheism or agnosticism (Pennycook, Ross, Koehler, & Fugelsang, 2016), liberal political preferences (Byrd & Białek, 2021;Deppe et al, 2015;Saribay & Yilmaz, 2017;Yilmaz & Alper, 2019), and the orthodox "Gettier intuition" about knowledge (Byrd & Cullen, 2021;Machery et al, 2017).…”
Section: Reflection and Philosophy Among Laypeoplementioning
confidence: 99%